Selectivity, Market Timing and the Morningstar Star-Rating System - Antonios Antypas; Guglielmo Maria Caporale; Nikolaos Kourogenis; Nikitas Pittis (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper evaluates the Morningstar mutual fund ranking system. We find that indeed higher Morningstar ratings are associated with higher returns on the portfolios including respectively five-, four-, three-, two- and one-star funds only (STAR5 to STAR1). We then perform an unconditional and conditional portfolio performance evaluation. In both cases the evidence suggests that the better performance of the STAR3, STAR4 and STAR5 categories reflects superior stock selection rather than market timing abilities. Overall, the implication for the Morningstar ranking system is that this is most effective in identifying the worst-performing funds (STAR1 or STAR2) rather than the best-performing ones.
Keywords: G23; 330; Mutual fund; Morningstar Star-Rating System; CAPM; conditional and unconditional portfolio performance evaluation; Investmentfonds; Bewertung; Performance Measurement; Wertpapieranalyse; Capital Asset Pricing Model; Theorie; Welt